1975
DOI: 10.1152/ajplegacy.1975.228.5.1510
|View full text |Cite
|
Sign up to set email alerts
|

Myo-inositol transport in the central nervous system

Abstract: Free myo-inositol (inositol) transport into the cerebrospinal fluid (CSF), brain, and choroid plexus and out of the cerebrospinal fluid was measured in rabbits. In vivo, inositol transport from blood into choroid plexus, CSF, and brain was saturable with an apparent affinity constant (K-t) of approximately 0.1 mM. The relative turnover of free inositol in choroid plexus (16 percent/h) was higher than in CSF 4percent/h) and brain (0.3percent/h) when meausred by tissue penetration of tracer [3-H]-labeled inosito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
2

Year Published

1979
1979
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(60 citation statements)
references
References 0 publications
1
57
0
2
Order By: Relevance
“…SMIT2, when expressed in oocytes, transports MI with a K m (120 M) closely corresponding to the 70 M human plasma concentration of MI (14) and well below the 470 M concentration reported for cerebrospinal fluid (37) and has a substantial I max that compares well with other sodium-coupled cotransporters. Furthermore, the K m for glucose is well above normal serum glucose levels.…”
Section: Fig 6 Phlorizin Inhibition Of MI Currentmentioning
confidence: 66%
“…SMIT2, when expressed in oocytes, transports MI with a K m (120 M) closely corresponding to the 70 M human plasma concentration of MI (14) and well below the 470 M concentration reported for cerebrospinal fluid (37) and has a substantial I max that compares well with other sodium-coupled cotransporters. Furthermore, the K m for glucose is well above normal serum glucose levels.…”
Section: Fig 6 Phlorizin Inhibition Of MI Currentmentioning
confidence: 66%
“…Brain levels of MI, however, are more than 20 times that of cerebrospinal fluid. Nevertheless, active transport has not been demonstrable with brain slices (11) and isolated brain synaptosomes (13). The uptake of MI by synaptosomnes was not saturable and was not inhibited by dinitrophenol or ouabain.…”
Section: Introductionmentioning
confidence: 91%
“…The brain contains the highest known concentration of nonphosphorylated MI of any tissue in the body but its mechanism of concentration remains in dispute. The blood brain barrier prevents free access of plasma MI into brain but Spector and Lorenzo (11) and Spector (12) have clearly demonstrated that both MI and sciyllo-inositol are accumulated within the choroid plexus by a single, specific, energy-requiring transport process that depends on intracellular reduced sulfhydryl bonds. After its concentration in the choroid plexus, MI apparently enters cerebral spinal fluid by simple diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Millions of different single chain antibodies on phages are used for isolating highly specific therapeutic antibody leads. One of the most successful examples was adalimumab (Abbott Laboratories), the first fully human antibody targeted to TNF alpha (Spector and Lorenzo, 1975).…”
Section: Applications Of Phage Display 421 General Applicationsmentioning
confidence: 99%